INTEGRASI NILAI HUMANISME DAN EGALITARIANISME PEMIKIRAN KAZI NAZRUL ISLAM DALAM PELAJARAN AGAMA ISLAM DI SDN 101470 SOBAR - Pasaribu, Yusti Andayati; Harahap, Rita Nur’Ain; Yusril, Rizky (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This research aims to analyze the integration of humanism and egalitarianism values from the thoughts of Kazi Nazrul Islam into Islamic religion lessons at SDN 101470 Sobar. These values aim to shape students' characters who are fairer, more caring and have high social awareness. The research method used is a qualitative approach with data collection techniques through observation, interviews and documentation. The research results show that integrating the values of humanism and egalitarianism is carried out through strengthening teaching materials, value-based learning methods, as well as strengthening the role of teachers as role models. However, there are obstacles in implementation, such as limited teacher understanding, conventional learning methods, and lack of support from school policies and parent participation. This research recommends strengthening the role of teachers through training and parental involvement in the formation of student character.